Development Challenges Confronting Pakistan - Edited by Weiss. Anita M. and Khattak, Saba Gul. (Boulder & London Kumarian Press, 2013)
The global scholarly community concerned with development and social transformation has identified explicit "structural impediments" that constrain countries' efforts to alleviate poverty and promote sustainable social development. The United Nations Development Programme, in launching its Millennium Development Goals, contends that there are "practical, proven solutions" to breaking out of the poverty traps that entangle poor countries. In Pakistan, there has been limited substantive research conducted to identify the unique blend of structural impediments to development that prevail in the country today. Indeed, Pakistan's prospects to promote viable, sustainable social development appear bleaker today than a decade ago. Development Challenges Confronting Pakistan seeks to rectify this void by bringing together scholars and practitioners--many of them from Pakistan--to provide a scholarly understanding of the structural impediments, or barriers, that have negative effects on Pakistan's ability to eliminate poverty, promote social justice and implement policies to promote equity. This book will be an essential tool for analysis, study and practice. Its publication is indeed a major event in South Asian scholarship
Include Index.
Keywords: Pakistan -- Human Security -- Politics and Government